Using functional analysis diagrams to improve product reliability and cost. (December 2016) - Michalakoudis, Ioannis; Childs, Peter; Aurisicchio, Marco; Harding, James
Failure mode and effects analysis and value engineering are well-established methods in the manufacturing industry, commonly applied to optimize product reliability and cost, respectively. Both processes, however, require cross-functional teams to identify and evaluate the product/process functions and are resource-intensive, hence their application is mostly limited to large organizations. In this article, we present a methodology involving the concurrent execution of failure mode and effects analysis and value engineering, assisted by a set of hierarchical functional analysis diagram models, along with the outcomes of a pilot application in a UK-based manufacturing small and medium enterprise. Analysis of the results indicates that this new approach could significantly enhance the resource efficiency and effectiveness of both failure mode and effects analysis and value engineering processes.